Matrix approach to noncommutative stably free modules and Hermite rings - Lezama, O.; Gallego, C. (Algebra and Discrete Mathematics, 2014)
In this paper we present a matrix-constructive proof of an Stafford’s Theorem about stably free modules over noncommutative rings. Matrix characterizations of noncommutative Hermite and projective-free rings are exhibit. Quotients, products and localizations of Hermite and some other classes of rings close related to Hermite rings are also considered.